Significance of neutrino-neutrino interaction in neutrino oscillation in core-collapse supernova - Prabandha Nakarmi; Jeevan Jyoti Nakarmi (Bibechana, 2014)
We study the possibility of neutrino-neutrino interaction inside the neutrino core of supernova (ρ ≥ 1010 g/cc) and outside the neutrinosphere. The angular dependence of the neutrino-neutrino interaction Hamiltonian causes multi-angle effects that can lead either to oscillation or free streaming of neutrinos. If the angle between interactions is π/2, the neutrinos are trapped inside neutrino core and chances of oscillation increases due to interaction. As the angle gradually changes, the chance of oscillation decreases and free streaming of neutrino can be observed out of core of supernova as shock waves.